Pengaruh Pelatihan, Kemampuan Teknik Pemakai Sistem Informasi Akuntansi dan Dukungan Manajemen Puncak Pada Kinerja Individual - Nita Adiyantari, Ni Made Ayu; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 27 No 3 (2019), 2019)
Employees who work in companies are expected to do their responsibility and gives accurate and reliable information on time. Factors that can affect the performance of each individual must always be considered by the company in order to achieve optimal individual performance. This research was conducted at PT. BPR Bank Kertiawan. The sampling technique used is a saturated sample technique. The number of respondents used is 80 employees. This study use multiple linear regression analysis as the analysis technique. The results of this study indicate that training, the ability to use SIA techniques, and top management support have a positive and significant influence on individual performance at PT. BPR Bank Kertiawan Keywords  : Training, top management support, AIS user technical capabilities, individual performance